Impact of Linguistic Environment on Speaking Skills of Female Students at the Arabic Language Center Islamic Boarding School in Indonesia - Lika Harnika; Zainal Abidin; Muhammad Fikri Maulana; Serli Saputri; Afna Mufidah Salsabila; Azron Azim (IAIN Palangka Raya, 2024)
The research emphasizes the effectiveness of Arabic language learning when supported by a social environment where Arabic is used daily. It aims to assess the linguistic environment and speaking skills at an Arabic Language Center within an Islamic Boarding School, as well as determine the impact of the environment on speaking skills. Using a quantitative approach with SPSS 22, the study employed a case study method for sampling, gathering data through observation, interviews, and documentation. Analysis involved processing questionnaires and drawing conclusions. Results showed a strong Arabic-speaking environment at the Islamic Boarding School, with 68.8% of students proficient in speaking skills. Speaking skills at the Arabic Language Center were very strong, especially among students from Arabic-speaking households, with 91.8% proficiency. A moderate correlation between environment and speaking skills was observed, indicating a relationship between the two variables among students at the center.
Keywords: arabic language center; Language and Literature; linguistic environment; P; arabic-speaking environment; 4. Education